An Efficient Hybrid Decision-making Model for Sustainable Supplier Selection (Case Study: Parts Supply Industry) - Mahboubeh Afzali (Environmental Energy and Economic Research)
Supplier selection has been considered as one of the important decisions taken by firms in supply chain management to enhance profitability in this competitive era. With the emergence of environmental policies and social concerns, companies are forced to consider triple bottom line including economic, environmental, and social attributes into their supply chain activities. Since different criteria affecting sustainable supplier selection conflict with each other, sustsainable supplier selection problem is considered as a multi-criteria decision-making problem. Furthermore, the evaluation of numerous conflicting requirements suffers imprecise and vague in decision makers’ judgments. In this paper, an efficient Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method which is integrated by gray theory is developed to deal with uncertainty and imprecise among decision makers’ judgments in the most right sustainable supplier selection. The proposed method was performed on tool industry as case study to select the most sustainable alloy supplier which involves three main criteria and twelve sub-criteria. The results indicated that Ara Sanat Asia company performs better than the other companies due to high contribution in the environmental and social criteria in addition to economic criteria as traditional metrics.